2022
DOI: 10.1108/cdi-11-2021-0283
|View full text |Cite
|
Sign up to set email alerts
|

A dual-pathway model for examining the effects of customer mistreatment on an employee's customer-directed counterproductive work behavior: can job autonomy make a difference?

Abstract: PurposeThis research examined how customer mistreatment activates individual customer-directed counterproductive work behavior (CWBC) by investigating the mediating roles of negative work reflection and negative affect. It also explored whether job autonomy buffers the negative impact of customer mistreatment on CWBC.Design/methodology/approachThe authors tested their predictions using an experience-sample method with a sample of data from 79 service workers across eight days. A multilevel structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Park and Kim (2019) demonstrated that customer mistreatment received during the workday is positively related to negative affect at the end of work. Likewise, Lu et al. (2023) also found a significant and positive relationship between daily experiences of customer mistreatment and negative affect in the evening.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 75%
“…Park and Kim (2019) demonstrated that customer mistreatment received during the workday is positively related to negative affect at the end of work. Likewise, Lu et al. (2023) also found a significant and positive relationship between daily experiences of customer mistreatment and negative affect in the evening.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 75%
“…Recently, Lu et al (2023) in their multi-time-lagged diary study, examine the mediating role of employees’ negative work reflection between customer mistreatment and customer-directed counterproductive work behaviors. Negative work reflection is the individual's unintentional thoughts about the negative facets of work such as negative work events (Fritz & Sonnentag, 2006).…”
Section: Findings and Discussionmentioning
confidence: 99%